Opa protein repertoires of disease-causing and carried meningococci - Callaghan, M; Buckee, C; McCarthy, N; Ibarz Pavón, A; Jolley, K; Faust, S; Gray, S; Kaczmarski, E; Levin, M; Kroll, J; Maiden, M; Pollard, A; et al. (American Society for Microbiology, 2008)
The meningococcal Opa proteins play an important role in pathogenesis by mediating invasion of human cells. The aim of this investigation was to determine whether carried and disease-associated meningococci possess different Opa repertoires and whether the diversity of these proteins is associated with clinical severity of disease. Opa repertoires in 227 disease-associated meningococci, isolated in the United Kingdom over a period of 6 years, were compared to the repertoires in 190 asymptomatically carried meningococci isolated in the United Kingdom from a contemporary, nonepidemic period. Multidimensional scaling (MDS) was employed to investigate the association between Opa repertoires and multilocus sequence typing (MLST) genotypes. Associations with clinical severity were also analyzed statistically. High levels of diversity were observed in opa alleles, variable regions, and repertoires, and MDS revealed that MLST genotypes were strongly associated with particular Opa repertoires. Individual Opa proteins or repertoires were not associated with clinical severity, though there was a trend toward an association with the opaD locus. Meningococcal Opa repertoire is strongly linked to MLST genotype irrespective of epidemiological sampling and therefore correlates with invasiveness. It is not, however, strongly associated with severity of meningococcal disease.